In-situ formed Li2O and an artificial protective layer on copper current collectors to enhance the cycling stability of lithium metal anode batteries - Darwaish, Kainat; Wu, Yi–Shiuan; Wu, She–Huang; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chun-Chen (Elsevier Ltd, 2024)
In this study, we present a facile one-step method for the thermal treatment of commercial Cu foils, leading to the growth of Cu2O and CuO nanoparticles in an air atmosphere, resulting in the coating of an artificial protective layer on the copper foil surface. The as-prepared CuO/Cu2O nanoparticles exhibit a spherical morphology, providing ample active sites to improve uniform lithium plating and cyclic stability by building a highly stable In-situ Li2O-rich solid-electrolyte interphase (ISEI). The artificial solid-electrolyte interphase (ASEI) protective layer contains graphene oxide (GO) as a filler with PVDF-HFP and lithium Nafion polymers, enhances Li+ ion migration, which reduces volume expansion and stabilizes the interface, preventing unwanted side reactions between active lithium and electrolytes by facilitating controlled lithium deposition underneath. For integration into an anode-less full cell based on a 2032-type coin cell, alongside a lithium iron phosphate (LFP) cathode, the ISEI oxide layer was grown on a Cu foil electrode (denoted as Cu-30) via a thermal treatment at 320 ◦C in air for 30 min and coated ASEI (denoted as GO@Cu-30). This cell demonstrated remarkable electrochemical performance. After 250 cycles at 0.5C, it exhibited an outstanding capacity retention of 93.12 % with 99.92 % CE, significantly surpassing the performance of a bare Cu foil, which showed a capacity retention of only 9.54 % with CE of 98.77 %. This work highlights the potential of a simple thermally treated Cu foil as a current collector to overcome the Anode-less lithium metal battery (ALMB) challenges associated with high-energy-density demand.